SU(3) Symmetry in hafnium isotopes with even neutron N=100-108 - I. Hossain; Fadhil I. Sharrad; Huda H. Kassim; Amir A. Mohammed-Ali; A. S. Ahmed (Institute of Advanced Engineering and Science, 2020)
In this paper, we have reviewed the calculation of ground states energy level up to spin 14+, electric quadrupole moments up to spin 12+, and reduced transition probabilities of Hafnium isotopes with even neutron N = 100-108 by Interacting Boson Model (IBM-1). The calculated results are compared with previous available experimental data and found good agreement for all nuclei. Moreover, we have studied potential energy surface of those nuclei. The systematic studies of quadrupole moments, reduced transition strength, yrast level and potential energy surface of those nuclei show an important property that they are deformed and have dynamical symmetry SU(3) characters.